Struggles under authoritarianism - Salloukh, Bassel F. (2007)
The failure of social science expectations that several Arab states would democratize in the 1980s and 1990s forced a reappraisal. The belief that chronic fiscal crisis and waning popular support would lead regimes to loosen authoritarian controls and thus possibly lead to democratization proved disappointingly unfounded. Instead, regimes that launched liberalizations in the 1980s reversed or halted most political-reform components in the following decade. Given that rising oil and commodity prices since 2003 have eased budgetary constraints for many states (especially in the Gulf), the emerging pattern is political change and shifts under authoritarian regimes over time, not democratization. A number of recent works have responded by quantitatively and qualitatively assessing factors that account for regional imperviousness to democratization as well as change in different directions. The purpose of this essay is to contribute to these responses in two ways: one, conceptualizing important change in state–society relations short of democratization; and two, comparatively analyzing the cases of Jordan, Kuwait, and Syria to propose ways of explaining these outcomes.